Analisis Prestasi Sepak Bola Di SMP Negeri 7 Tanjung Jabung Timur - Pratami, Putri Desmalinda; Saputra, Endarman; Adrizal, Mohd (Dharmas Journal of Sport, 2026)
This study aims to analyze soccer achievements at SMP Negeri 7 Tanjung Jabung Timur by identifying how students achieve these achievements and the factors that influence them. The research method used was descriptive qualitative with data collection techniques through interviews and documentation of soccer team students, physical education teachers, and coaches. The results of the study show that achievements are obtained through intensive training and sparring, periodic evaluations, and high self-confidence with social support. Factors influencing performance include: (1) a planned athlete development system with selection based on physical ability, technique, and experience; (2) optimization of limited facilities and infrastructure by borrowing village fields; (3) moral and material support from families and the community; (4) systematic training management covering technical, tactical, physical, and mental aspects; and (5) high student motivation. The conclusion of the study is that despite limited facilities and infrastructure, soccer achievements can still be achieved with a good coaching system, positive environmental support, structured training management, and high student motivation. It is recommended that the government and schools improve the quality of teacher/coach training and conduct continuous evaluations to improve skills in coaching competitive sports.